DDX39B promotes translation through regulation of pre-ribosomal RNA levels. Issue 9 (2nd September 2018) - Awasthi, Sharad; Chakrapani, Baskar; Mahesh, Arun; Chavali, Pavithra L.; Chavali, Sreenivas; Dhayalan, Arunkumar
ABSTRACT: DDX39B, a DExD RNA helicase, is known to be involved in various cellular processes such as mRNA export, splicing and translation. Previous studies showed that the overexpression of DDX39B promotes the global translation but inhibits the mRNA export in a dominant negative manner. This presents a conundrum as to how DDX39B overexpression would increase the global translation if it inhibits the nuclear export of mRNAs. We resolve this by showing that DDX39B affects the levels of pre-ribosomal RNA by regulating its stability as well as synthesis. Furthermore, DDX39B promotes proliferation and colony forming potential of cells and its levels are significantly elevated in diverse cancer types. Thus, increase in DDX39B enhances global translation and cell proliferation through upregulation of pre-ribosomal RNA. This highlights a possible mechanism by which dysregulation of DDX39B expression could lead to oncogenesis.